Dato’ Haji Abdul Hak @ Abdul Ghani Abdullah : Penglibatan Dan Gaya Bacaan Dalam Seni Lagu Al-Quran - Mohd Zaini Zakaria; Khairul Anuar Mohamad; Adnan Mohamed Yusoff; Norazman Alias (Universiti Sains Islam Malaysia, 2024)
PAPER PROCEEDINGS THE 7TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION (SWAT) 2021 “ISLAMIC AND NON-REVEALED KNOWLEDGE IN FACING THE GLOBAL CHALLENGES” 6th – 7th October 2021 / 29 – 30 Safar 1443H Faculty of Quranic and Sunnah Studies Universiti Sains Islam Malaysia